The natural absence of RPA1N domain did not impair Leishmania amazonensis RPA-1 participation in DNA damage response and telomere protection. - Da Silveira, Rita de Cássia Viveiros; Da Silva, Marcelo Santos; Nunes, Vinícius Santana; Perez, Arina Marina; Cano, Maria Isabel Nogueira (Cambridge University Press (CUP), 2013)
We have previously shown that the subunit 1 of Leishmania amazonensis RPA (LaRPA-1) alone binds the G-rich telomeric strand and is structurally different from other RPA-1. It is analogous to telomere end-binding proteins described in model eukaryotes whose homologues were not identified in the protozoan's genome. Here we show that LaRPA-1 is involved with damage response and telomere protection although it lacks the RPA1N domain involved with the binding with multiple checkpoint proteins. We induced DNA double-strand breaks (DSBs) in Leishmania using phleomycin. Damage was confirmed by TUNEL-positive nuclei and triggered a G1/S cell cycle arrest that was accompanied by nuclear accumulation of LaRPA-1 and RAD51 in the S phase of hydroxyurea-synchronized parasites. DSBs also increased the levels of RAD51 in non-synchronized parasites and of LaRPA-1 and RAD51 in the S phase of synchronized cells. More LaRPA-1 appeared immunoprecipitating telomeres in vivo and associated in a complex containing RAD51, although this interaction needs more investigation. RAD51 apparently co-localized with few telomeric clusters but it did not immunoprecipitate telomeric DNA. These findings suggest that LaRPA-1 and RAD51 work together in response to DNA DSBs and at telomeres, upon damage, LaRPA-1 works probably to prevent loss of single-stranded DNA and to assume a capping function.
Keywords: nucleic acid synthesis inhibitor; phleomycin; protozoal protein; cell cycle checkpoint; double stranded DNA break; drug effect; genetics; Leishmania; metabolism; nick end labeling; telomere; Cell Cycle Checkpoints; DNA Breaks, Double-Stranded; In Situ Nick-End Labeling; Nucleic Acid Synthesis Inhibitors; Phleomycins; Protozoan Proteins; Telomere